Effect of Floating Debris on Local Scour at Bridge Piers - Mahmoud Saleh. Al-Khafaji; Ali S. Abbas; Rusul I. Abdulridha (Engineering and Technology Journal, 2016)
This research studied the effects of dimensions and shapes of debris accumulations on river’s bed scour at bridge piers by preparing and operating physical model and compared the results with that of applying a one-dimensional steady flow mathematical model using HEC-RAS software to the same geometry and boundary conditions of the physical model. TheResults of studying three shapes of accumulation floating debris (wedge, rectangular and trapezoidal) on bridge pier using physical model show that the dimensions and shapes of accumulation debris have a clear effect on the patterns of bed scour and the maximum scour depth at the pier.There is a big difference between the measured and computed scour depths using the physical and the HEC-RAS models where the software exaggerates in the calculation of the scour depths and the widths of scour hole without taking into consideration the effect of debris shape on the shape of scour hole.